Monitoramento de danos estruturais utilizando sensores de nanocompósitos - Takiuti, Breno Ebinuma [UNESP] (2015)
With the objective of structural health monitoring (SHM) in aerospace structures, several monitoring techniques have been studied. One of the most recent techniques is based on the use of continuous sensors, made of thin films of nanocomposites. The advantage of using such materials is the possibility to apply them on complex surfaces, covering larger areas and using few acquisition terminals. Moreover, by using the nanocomposites, it is possible to control its mechanical and electrical properties, making it possible to create a customized sensor for each case. The nanocomposite found most commonly in the literature for damage detection are the carbon nanotubes (CNT) composites, while the matrix depends on each case. This work proposes the use of alternative materials such as the ITO (Indium tin oxide) nanowires inserted at PMMA (Poly(methyl methacrylate)) to be used as coatings for the monitored structure. In order to verify the effectiveness of this sensor, several tests were proposed. These tests consists on monitoring the nanocomposite's behavior when affected by some kind of damage, in which can be simulated by a mass addition, excess of load or a crack. The principle for the damage detection is to measure the electrical resistance between two points at the film sensor and verify the variations caused by the damage to these measurements. In general, the obtained resistances varied from 1kΩ to 10kΩ, while with the damage appearance the measurements varied more than 30% at the path with the damage and at the paths nearby. Tests at the environmental chamber, with temperature and humidity control, showed that the sensor is sensitive to high temperatures and humidity levels. Regarding the sensibility to stress applied to the plate, the sensor showed changes at the resistances only when the plate started to deform plastically. The obtained results are promising and indicate that this method is effective for damage detection